A review of management strategies for nociceptive and neuropathic ocular surface pain (2020)
Despite being a common presenting symptom to eye-care clinics, many ophthalmologists have difficulty diagnosing and managing ocular surface pain. The purpose of this review is to discuss potential causes of ocular surface pain, focusing on both nociceptive and neuropathic aetiologies. Specifically, we outline an approach to the diagnosis of ocular surface pain and focus on various management strategies, providing supporting evidence on the efficacy of various treatments.